Simultaneous Relationships Between Corporate Governance Practice and Firm Value - Cynthia Afriani Utama; Handy Handy (The Indonesian Journal of Accounting Research, 2013)
The main purpose of this study is to investigate whether there is a simultaneous relationship between Corporate Governance (CG) practice and firm value. This study also investigates: 1) the effect of risks and firm profitability on firm value; and 2) the effect of ownership structure (i.e., regulated, state-owned-entreprise (SOE), foreign, and institutional investors) and company size on CG practice. Based on the corporate governance scores rated by the Institute of Indonesian Corporate Directorship (IICD) in 2005, the study finds that  corporate governance practice provides a positive effect on firm value, but not vice versa. This study also shows that: 1)  firm value is affected positively by  profitability but not affected negatively by  risk; and 2) the types of ownership structure, i.e. SOE, foreign, and regulated industry enhance  CG practice. Finally,  company size  positively affects  CG practice. Meanwhile, the study fails to find a positive association between ownership by institusional investors and CG practice.